Influence of Fill Gap on Flexural Strength of Parts Fabricated by Curved Layer Fused Deposition Modeling. (2015) - Guan, Hua Wei; Savalani, Monica Mahesh; Gibson, Ian; Diegel, Olaf
Abstract: Rapid Prototyping Techniques (RPT) have evolved over the last decade. Novel RP techniques are being developed to improve the overall properties of parts manufactured using RPT. One such technique is the Curved layer fused deposition modeling (CLFDM) which has been developed based on the conventional Fused Deposition Modeling (FDM) technique. The CLFDM technique has gained significant amount of attention as a result of its advantages such as increased flexural strength, reduction of the stair-stepping effect and the reduction in the number of layers, especially for thin shell-like structures. This paper studies the effects of fill gap (FG) on flexural strength and bead dimension, middle-plane cross section profiles and the fracture surface and compares the results to parts made using the traditional planar layer-by-layer approach. Also, in the end some meaningful and interesting future study areas both in hardware design and software development for the CLFDM are proposed.